2016
DOI: 10.1016/j.bpj.2016.02.027
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Basepair Mismatch on DNA Strand Displacement

Abstract: DNA strand displacement is a key reaction in DNA homologous recombination and DNA mismatch repair and is also heavily utilized in DNA-based computation and locomotion. Despite its ubiquity in science and engineering, sequence-dependent effects of displacement kinetics have not been extensively characterized. Here, we measured toehold-mediated strand displacement kinetics using single-molecule fluorescence in the presence of a single basepair mismatch. The apparent displacement rate varied significantly when th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 47 publications
3
35
0
3
Order By: Relevance
“…19 However, the only previous attempt to systematically probe the consequences of mismatch repair did not see any signal of enhanced displacement, due to the use of much longer toeholds. 30 Interestingly, we note that oxDNA predicts reaction acceleration even for longer toeholds if concentrations are high enough to access the first order limit (Supplementary Material S1.2). In this context, mismatch repair might be used to increase the fundamental speed limit of displacement reactions occuring, for example, at high effective concentrations between surface-localized reactants.…”
Section: Discussionmentioning
confidence: 85%
“…19 However, the only previous attempt to systematically probe the consequences of mismatch repair did not see any signal of enhanced displacement, due to the use of much longer toeholds. 30 Interestingly, we note that oxDNA predicts reaction acceleration even for longer toeholds if concentrations are high enough to access the first order limit (Supplementary Material S1.2). In this context, mismatch repair might be used to increase the fundamental speed limit of displacement reactions occuring, for example, at high effective concentrations between surface-localized reactants.…”
Section: Discussionmentioning
confidence: 85%
“…This prediction is consistent with the results of Broadwater et al, who observed no kinetic consequences of mismatch elimination when using toeholds of length 10 (ref. 30 ).…”
Section: Resultsmentioning
confidence: 99%
“…9a). A probe containing a hairpin has a higher target specificity than an unmasked probe with the same cognate sequence 1,43,44 ( Supplementary Figs. 15 and 16).…”
Section: Resultsmentioning
confidence: 99%